Cloning, expression, and characterization of a new pH‐ and heat‐stable alginate lyase from Pseudoalteromonas carrageenovora ASY5. Issue 7 (15th May 2019) - Zeng, Jie; An, Ding; Jiao, Chao; Xiao, Qiong; Weng, Huifen; Yang, Qiuming; Xiao, Anfeng
Abstract: Alginate lyase is important in marine alginate degradation, and its enzymatic hydrolysates are excellent antioxidants. Here, we cloned a new alginate lyase, that is, Alg823, from the Gram‐negative marine bacterium Pseudoalteromonas carrageenovora ASY5. The optimal temperature and pH of Alg823 were 55°C and pH 8.0, respectively. After 30 min of incubation at 50°C, Alg823 could maintain over 75.0% of the maximum enzyme activity, suggesting its thermostability. The recombinant alginate lyase retained more than 80.0% of the maximum enzyme activity after it was treated at pH 6.0–10.0 and 4°C for 24 hr, indicating its excellent pH stability. Mg 2+, Ca 2+, Na +, and K + could promote enzyme activity. Alginate oligosaccharides obtained by degradation with Alg823 displayed an excellent ability to scavenge ABTS, hydroxyl, and DPPH radicals. Alg823 showed potential for novel applications in alginate oligosaccharide production because of its pH tolerance and heat adaptation. Practical applications: Alginate oligosaccharides produced by alginate degradation possess favorable properties, such as low molecular weight, high stability, and co‐dissolution with water. These oligosaccharides also have many biological activities. As such, they have been widely explored. Alginate oligosaccharides are prepared via three methods, namely, physical, chemical, and enzymatic methods. In chemical method, operational processes are difficult to thereby possibly damaging the unique structure of polysaccharides and causing environmental pollution. Although physical methods can overcome some of the shortcomings of chemical methods, their reaction is still difficult to control, and products are complicated. Conversely, enzymatic methods can has advantages of mild conditions, single product, and less pollution. Furthermore, oligosaccharides prepared by enzymatic methods are more biologically active than those prepared by other methods. Thus, finding novel alginate lyase with high activity and stability is important for research and commercial purposes.